1997
DOI: 10.1002/(sici)1097-4679(199701)53:1<65::aid-jclp9>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the inventory of suicide orientation-30 (ISO-30) for adolescent psychiatric inpatients: Linking clinical decision making with outcome evaluation

Abstract: This report describes a study that integrates program evaluation with clinical practice. The subjects were 139 adolescent psychiatric inpatients who were tested with the Inventory of Suicide Orientation-30 (ISO-30) at admission and retested six days after admission. Aggregate analyses showed statistically significant changes in the direction of decreased suicidality on all ISO-30 indices. Further analyses compared the data with normative data from the ISO-30 manual, and also evaluated the relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…To evaluate suicidal orientation, we used the ISO‐30 (King & Kowalchuk, , Brazilian version of Silva et al, in press), which is a self‐reported instrument with 30 items, with an internal consistency of 0.84. It was developed using two samples of adolescents in both clinical and school settings (King, & Kowalchuk, ), and it has been validated in clinical (King, & Kowalchuk, ; Osman et al, ; Piersma, & Boes, ) and community student samples (Casullo, ; King, & Kowalchuk, ; Liporace, & Casullo, ; Paniagua‐Suárez, González‐Posada, & Rueda‐Ramírez, ). ISO‐30 has adequate convergent, discriminant, and predictive validity (King, & Kowalchuk, ; Osman et al, ; Paniagua‐Suárez et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate suicidal orientation, we used the ISO‐30 (King & Kowalchuk, , Brazilian version of Silva et al, in press), which is a self‐reported instrument with 30 items, with an internal consistency of 0.84. It was developed using two samples of adolescents in both clinical and school settings (King, & Kowalchuk, ), and it has been validated in clinical (King, & Kowalchuk, ; Osman et al, ; Piersma, & Boes, ) and community student samples (Casullo, ; King, & Kowalchuk, ; Liporace, & Casullo, ; Paniagua‐Suárez, González‐Posada, & Rueda‐Ramírez, ). ISO‐30 has adequate convergent, discriminant, and predictive validity (King, & Kowalchuk, ; Osman et al, ; Paniagua‐Suárez et al, ).…”
Section: Methodsmentioning
confidence: 99%